2010
DOI: 10.1021/nl902228p
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Concentration of DNA Polymers in Nanofluidic Channels

Abstract: DNA molecules can be concentrated in a narrow region of a nanochannel when driven electrokinetically in submillimolar salt solutions. Transport experiments and theoretical modeling reveal the interplay of electrophoresis, electro-osmosis, and the unique statistical properties of confined polymers that lead to DNA aggregation. A finite conductance through the bulk of the device also plays a crucial role by influencing the electric fields in the nanochannel. We build on this understanding by demonstrating how a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 42 publications
6
71
0
Order By: Relevance
“…It is based on the fact that the velocities of EO and EP are opposite for DNA, inducing an enhancement of DNA concentration at the location where the velocities of EO and EP are of the same magnitude. Stein et al 18 found DNA aggregation in nanochannels by using similar method of force balancing. However, it is very difficult to create a condition in which EO mobility and EP mobility are exactly identical in magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the fact that the velocities of EO and EP are opposite for DNA, inducing an enhancement of DNA concentration at the location where the velocities of EO and EP are of the same magnitude. Stein et al 18 found DNA aggregation in nanochannels by using similar method of force balancing. However, it is very difficult to create a condition in which EO mobility and EP mobility are exactly identical in magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate these limitations, various techniques have been reported in a form of miniaturized system. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The conventional way to enhance the sensitivity of detection is to increase the copy number of DNA by the chemical amplification through polymerase chain reaction ͑PCR͒. [1][2][3] However, various components are necessary in PCR chemistry, such as enzymes and primers as well as precise temperature control.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Sample preconcentration exploits various sample characteristics, including electric charge, size, mobility, and affinity. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] DNA has the unique property of having a uniform charge to size ratio, making charge selective preconcentration efficient. Among the preconcentration techniques using the electric property of DNA, the electrokinetic trapping technique has received much attention due to its high sensitivity and easy miniaturization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Previous work has also used single molecule fluorescence for hydrodynamic studies in nanochannels. 11 In this paper, we demonstrate simultaneous ionic current and fluorescent detection of DNA translocation through glass nanocapillaries. These have been shown to be an alternative to traditional solid state nanopores.…”
mentioning
confidence: 99%